Interpolation Problems for Random Fields from Observations in Perforated Plane - Moklyachuk, M.P.; Shchestyuk, N.Yu.; Florenko, A.S. (Математичне та комп'ютерне моделювання. Серія: Технічні науки, 2016)
The problem of estimation of linear functionals which depend on the unknown values of a homogeneous random field ξ(k, j) in the region K ⊂ Z² from observations of the sum ξ(k, j)+η(k, j) at points (k, j)  Z²\K is investigated. Formulas for calculating the mean square errors and the spectral characteristics of the optimal linear estimate of functionals are derived in the case where the spectral densities are exactly known. Formulas that determine the least favourable spectral densities and the minimax (robust) spectral characteristics are proposed in the case where the spectral densities are not exactly known while a class of admissible spectral densities is given. Досліджується задача оцінювання лінійних функціоналів від невідомих значень однорідного випадкового поля ξ(k, j) для області K ⊂ Z² за спостереженями суми полів ξ(k, j)+η(k, j) в точках (k, j)  Z²\K. Знайдено формули для обчислення середньоквадра- тичної похибки та спектральної характеристики оптимальної лінійної оцінки функціола у випадку відомих спектральних щільностей полів. Запропоновано формули для визначення найменш сприятливої спектральної щільності та мінімаксної (робастної) спектральної характеристики у випадку, коли спектральна характеристика точно не відома, але клас спектральних характеристик, до якого належить спектральна щільність визначено.